Comparison of diagnosis of temporomandibular joint disorders based on RDC/TMD Axis I and DC/TMD Axis I - Lestari, Brigitta Swasti; Rikmasari, Rasmi; Bonifacius, Setyawan (Indonesia Prosthodontic Association, 2021)
Introduction: The Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) has become the most widely used diagnostic protocol for research in temporomandibular disorders (TMD). The invalidity of RDC/ TMD in clinical application causes the revision of RDC/TMD to be the Diagnostic Criteria for Temporomandibular Disorder (DC/TMD). The purpose of this study was to determine the differences in diagnosis of TMD between RDC/ TMD examination and DC/TMD Axis I on students of Faculty of Dentistry, Padjadjaran University. Method: The type of this research was comparative survey approach using clinical examinations and questionnaires. The sample was collected from 48 people using random sampling techniques. The diagnosis of TMD was obtained by filling in the symptom questionnaire and clinical examination based on RDC/TMD Axis I and DC/TMD Axis I, which is then entered into the RDC/TMD diagnosis algorithm and DC/TMD decision tree. Results: The results showed that from 48 samples there were 36 (75%) people with the same diagnosis of RDC/TMD and DC/TMD, and 12 (25%) people with different diagnoses between RDC/TMD and DC/TMD. Conclusions: Based on the results of the study, the diagnosis of TMD based on RDC/TMD were still categorized the same as the diagnosis based on DC/TMD.